Visible light-induced oxidative N-dealkylation of alkylamines by a luminescent osmium(vi) nitrido complex. Issue 43 (21st October 2021) - Xiang, Jing; Peng, Min; Pan, Yi; Luo, Li-Juan; Cheng, Shun-Cheung; Jin, Xin-Xin; Yiu, Shek-Man; Man, Wai-Lun; Ko, Chi-Chiu; Lau, Kai-Chung; Lau, Tai-Chu
Abstract : The visible light-induced N -dealkylation of various alkylamines by a luminescent osmium(vi ) nitrido complex has been investigated. We provide definitive evidence that these reactions occur via an ET/PT mechanism. Abstract : N -Dealkylation of amines by metal oxo intermediates (MO) is related to drug detoxification and DNA repair in biological systems. In this study, we report the first example of N -dealkylation of various alkylamines by a luminescent osmium(vi ) nitrido complex induced by visible light.